Membaca Pemikiran Arkoun Tentang Etika Politik Islam - Yunus Rahawarin (Universitas Islam Negeri Alauddin Makassar, 2015)
Lack of concern towards ethics in politics is a major problem occurring in political practice. This, indeed, opposes the noble mission of politics as an art of state management. Hence, it needs a commitment to deal with political ethics as a behavior synergic with political acts. Moreover, it is necessary to consider that political ethics should ideally become political identity. Based on this, this article will discuss political ethics in contemporary Islam based on Mohammed Arkoun's perspective. Through content analysis of his works, this article will explore Arkoun's criticism toward established concept of